Development of Single‐Molecule Magnets - Shao, Dong; Wang, Xin‐Yi (Chinese journal of chemistry, 2020)
Main synthetic approaches and representative results in the design and synthesis of high performance single‐molecule magnets (SMMs) were highlighted in this concise review, which will give the readers a snapshot of the representative researches in this exciting field. Single‐molecule magnets (SMMs) are paramagnetic molecules that can be magnetized below a certain temperature and have potential applications in high‐density information storage, magnetic qubits, spintronic devices, etc. The discovery of the first SMM, Mn12, opened a new era of molecular magnetism and promoted collaborative researches between chemists and physicists for their exotic quantum as well as classical magnetic properties. In the recent past, great efforts have been made to develop strategies for constructing new SMMs with high energy barriers (Ueff) and blocking temperatures (TB), resulting in great and fast development of SMMs. In this concise review, we highlight the main synthetic approaches and representative results in the design and synthesis of high performance SMMs. We hope to give the readers a basic understanding of SMMs and a snapshot of the representative researches on SMMs from a perspective of synthetic chemists.